2016
DOI: 10.1002/art.39450
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcomes Among Participants in the WEGENT Trial of Remission‐Maintenance Therapy for Granulomatosis With Polyangiitis (Wegener's) or Microscopic Polyangiitis

Abstract: Objective. Findings from the WEGENT trial and other short-term studies have suggested that azathioprine (AZA) or methotrexate (MTX) could effectively maintain remission of granulomatosis with polyangiitis (Wegener's) (GPA) or microscopic polyangiitis (MPA).This study was undertaken to examine whether differences in rates of relapse or adverse events would appear after discontinuation of these 2 maintenance regimens, when assessed over a longer followup period.Methods. Long-term outcomes in patients enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 48 publications
3
74
1
8
Order By: Relevance
“…These data suggest that ANCA specificity (MPO or PR3) is a better predictor of relapse risk than diagnosis (GPA or MPA). This observation is also supported by data from other studies where increased relapse risk has been described to be associated mainly with PR3‐ANCA . A previous study described GPA (which is predominantly associated with PR3) as being associated with relapse as well .…”
Section: Discussionsupporting
confidence: 82%
“…These data suggest that ANCA specificity (MPO or PR3) is a better predictor of relapse risk than diagnosis (GPA or MPA). This observation is also supported by data from other studies where increased relapse risk has been described to be associated mainly with PR3‐ANCA . A previous study described GPA (which is predominantly associated with PR3) as being associated with relapse as well .…”
Section: Discussionsupporting
confidence: 82%
“…So far, the significance of PR3‐ANCA in GPA relapse has been debated among a number of previous studies. One study asserted that PR3‐ANCA positivity, but not GPA itself, might be independently associated with the relapse rate of GPA . Another study insisted that the increased titer of PR3‐ANCA might be closely associated with renal relapse, but not non‐renal relapse; a sub‐group analytic study presented a different view that the risk of relapse was associated with the type of AAV, but not the type of ANCA .…”
Section: Discussionmentioning
confidence: 99%
“…One study asserted that PR3-ANCA positivity, but not GPA itself, might be independently associated with the relapse rate of GPA. 26 Another study insisted that the increased titer of PR3-ANCA might be closely associated with renal relapse, but not non-renal relapse; 27 a subgroup analytic study presented a different view that the risk of relapse was associated with the type of AAV, but not the type of ANCA. 28 In addition, ethnic difference could also contribute to the discrepancy of factors affecting relapse rate of GPA between our study and previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…All ANCA assays were performed in local centres according to local protocols and reported as present or absent according to local upper limits of normal. Patients who were positive for both PR3- and MPO-ANCA on ELISA were classified as PR3-ANCA as previous studies have suggested that the presence or absence of PR3-ANCA is a significant predictor of relapse [15, 16]. …”
Section: Methodsmentioning
confidence: 99%